Legislative Guarantees to Empower Women to Hold Public Office and Reduce the Gender Gap - Khalifa, Hanan; Binmadi, Raniya Abood Binmadi (Journal of Legal Sciences, 2025)
This study aims to explore the concept of the empowerment of working woman as a critical pillar in the development and evolvement of the society, in addition to examining the challenges women face in enabling them to hold public positions; then to identify the legal principles established by the Saudi Law to achieve the principle of gender equality; and finally to demonstrate the legal rights granted by the Saudi Law to working women; accordingly, the researcher relied on the descriptive and analytical approach as a methodology for the research, The researcher reached several results, the most important of which are: The Saudi legislator has been keen to implement the principle of equality for working women in terms of rights and duties within the workplace, emphasizing that women should be treated equally with men. The legislator implemented this by using the term "worker," which encompasses both genders. The Kingdom has been keen to integrate women into comprehensive development plans, making their support and empowerment key objectives of Saudi Vision 2030. Therefore, the Saudi Law has focused on women’s participation in political, legislative, and economic life by appointing women to leadership positions in the Kingdom. The researcher recommended the need to enhance women’s self-efficacy through their participation in numerous training programs and practical courses that qualify them to make and take decisions. The researcher also recommended the need to shed light on the distinguished leadership models of Saudi women who have contributed to decision-making and occupying leadership positions via mass media, in order to change society’s perception of women and their effective role in the political, economic, and social domains.